PROTECTIVE EFFECTS OF GUAVA FRUIT ON THE HISTOPATHOLOGY REPRODUCTIVE ORGANS OF RATS EXPOSED TO 2,3,7,8 TETRACHLORODIBENZO-P-DIOXIN - Rani, Wahyu Indah Sulistya; Wurlina; Sri Mulyati; Budi Utomo; Tatik Hernawati; Ema Safitri; Wahyuningtyas, Puput Ade; mufa, Romy Muhammad Dary; Wahyuningtyas, Mila Nursadida; Wahyuningtyas, Yuanara Augusta (Buletin Veteriner Udayana, 2025)
Dioxin Toxicity has been studied to affect reproductive organ damage, so it can increase oxidative stress in the body. Guava fruit has several antioxidant compounds that can help break the chain of oxidative stress. The aim of this study was to determine the potential of guava fruit (Psidium guava L.) on Spermatogenik cell, Sertoli cell, and Leydig cell white rats exposed by TCDD. A total of twenty five white rats randomly divided to 5 groups, the Control group (K) which was given aquadest a dose 0.5 ml, Treatment group 0 (P0) which was given TCDD 100µg/KgBW solution a dose 0.5 ml, Treatment group 1 (P1) which was given guava fruit juice with a concentration of 25% a dose 0, 5 ml, treatment group 2 (P2) which was given guava fruit juice with a concentration of 50% a dose 0.5 ml, treatment group 3 (P3) which was given guava fruit juice with a concentration of 100% a dose 0.5 ml and the three groups were given a TCDD solution of 100µg/KgBW a dose 0.5 ml four hours before the treatment dose was given with 5 replicates in each group. Based on the results showed from this study that the administration of guava fruit juice at concentration 100% can efficiently affect the number of Spermatogenik cells consisting of Spermatogonium cells, Spematocyte cells, Spermatid cells in male white rats (Rattus norvegicus) exposed to 2,3,7,8, Tetrachlorodibenzo-P-dioxin.